POTENTIAL PROBLEMS IN GENERIC SUBSTITUTION OF ANTIEPILEPTIC DRUGS: SYSTEMATIC REVIEW - ., MEILANI; ICHSAN, BURHANNUDIN (International Journal of Applied Pharmaceutics, 2025)
This research aims to identify potential problems arising from substituting generic Antiepileptic Drugs (AEDs). The systematic review utilized databases including PubMed, Science Direct, Google Scholar, ProQuest, and Scopus. Search keywords encompassed (Epilepsy OR “Seizure Disorder” OR Aura) and (“Drug Substitution” OR “Therapeutic Substitutions” OR “Drug Switching” OR “Generic Substitution” OR “Generic Substitutions”) and (Brand). The inclusion criteria were all journals related to generic substitution of AEDs, research journals published from May 2015 to March 2022, and potential problems related to the bioequivalence of generic antiepileptic drugs and clinical outcomes therapy in epilepsy patients after generic substitution of antiepileptic drugs. Clinical outcomes can be seizure frequency, Adverse Events (AEs), Quality of Life (QoL), electroencephalogram (EEG) examination, laboratory evaluation, switchback rate, and emergency room visits. A total of 1,010 articles were identified, and 15 full-text articles were included for analysis. Most studies found no significant differences in seizure frequency, AEs, EEG findings, or laboratory results before and after substitution. Moreover, generic substitution did not adversely affect QoL. Although a small percentage of patients reverted to branded drugs, the switchback rate was minimal, and no notable increase in emergency room visits was reported. Overall, the substitution of generic AEDs is clinically safe and effective, with no significant impact on patient outcomes.